Post-Mortem Computed Tomographic Features of the Most Caudal Lumbar Vertebrae, Anatomical Variations and Acquired Osseous Pathological Changes, in a Mixed Population of Horses - Nicola Scilimati; Giovanni Angeli; Antonio Di Meo; Cecilia Dall’Aglio; Marco Pepe; Francesca Beccati (Animals, 2023)
The radiographic, ultrasonographic, and scintigraphic findings of horses with thoracolumbosacral pain have been previously reported. In this study, the computed tomographic appearance of anatomical variations and pathological changes of the equine caudal lumbar region through a post-mortem examination were investigated. A total of 40 horses that had died or were submitted for euthanasia, for reasons unrelated to the study, were included in the study. From all the specimens, the modified vertebral system was adopted to evaluate and describe the four most caudal lumbar vertebrae, which were numbered from a caudal reference point (lumbosacral junction), with the segment number designated within parentheses (i.e., L(i)-L(iv)). Contact of the spinous processes was detected in 21 specimens (54%) and fusion in 6 specimens (15%). Lumbar spondylosis was seen in 17 specimens (42.5%), more commonly on the lateral aspect or on both ventral and lateral aspects in 12 specimens (71%). The presence of spondylosis was found more commonly in older horses (p < 0.001). There was no difference in bony density in specimens with spondylosis or spinous processes contact compared to specimens without. The highest prevalence of bony changes was found at L(ii)-L(i) intertransverse joints in 28 specimens (97%) on the left and in 22 specimens (96%) on the right side. Spondylolisthesis and partial fusion of the L(ii)-L(i) vertebral disc were found in association with degenerative pathologies. This study showed a high frequency of several anatomical variations and acquired osseous pathological changes in the most caudal lumbar vertebrae via a CT examination.